(untitled) (Journal of Economic Research & Business Administration, 2022)
The development of e-commerce in recent years is associated with the digitalization and informatization of the world market. The coronavirus pandemic, lockdowns and quarantines in countries contributed to a reduction in retail and catering, as well as an increase in the share of e-commerce. The purpose of this article is to study the development of e-commerce and its impact on the global and Kazakhstani retail markets. The main areas of research are to study the e-commerce market in the context of digitalization and informatization of society. The idea of the study is to determine the main trends in the development of e-commerce in the global and Kazakhstani economies. The scientific significance of the study lies in the study of the main factors in the development of e-commerce in the context of multi-channel retail in Kazakhstan. The practical significance of the study is determined by the analysis of data on the development and expansion of e-commerce in the world and Kazakhstani markets. The study was conducted based on materials from official sources, scientific and practical publications, publications of state bodies and international organizations. The research methodology is presented by analysis, generalization, systematization and assumptions, in accordance with which the ways of development of e-commerce in modern conditions were determined. The main results of the study are presented in the conclusions and recommendations. The value of the study is in the analysis of development directions and expansion of e-commerce opportunities in the context of multi-channel retail. The practical significance of the results of the work is in the development of e-commerce and multichannel retail in Kazakhstan. Key words: e-commerce, multi-channel retail, digitalization, e-commerce.